PSIX-3 Effect of a combination of brown, green and red seaweeds on performance of nursery and growing-finishing pigs, and on carcass characteristics. (30th November 2020) - Manu, Hayford; Huang, Qiang; Pangeni, Devi; Owusu-Asiedu, Augustine; Sands, Jason; Baidoo, Samuel Kofi
Abstract: The objective of the study was to investigate the effect of a proprietary combination of brown, green and red seaweeds OceanFeed TM Swine (OFS) as a replacement of in-feed antibiotic growth promotors (AGP) or pharmacological levels of zinc oxide on performance of nursery and growing finishing pigs and carcass characteristics. Three hundred and twenty crossbred piglets (5.88 ± 0.26 kg) were blocked by BW and randomly allotted to 1 or 4 dietary treatments of low ZnO and no AGP but formulated to meet NRC (2012) nutrient requirements (Negative control (NC, T1)), NC + OFS (0.75 % in the nursery and 0.5% in the grower-finisher) (T2), NC + high ZnO + OFS (T3), Positive control (PC), formulated to meet NRC (2012) nutrient requirements + high ZnO + AGP, (T4). All data were analyzed using PROC MIXED procedure of SAS (version 9.4; SAS Inst., Inc., Cary, NC). The model included fixed effect of treatment and random effect of replicate. Pen with 8 pigs was the experimental unit. Adjustment for multiple comparisons was by Tukey Kramer's method. Overall (d 0 to 149), pigs on T4 diets had greater (0.47 vs 0.50; P = 0.013) and tended to have greater (0.48 vs 0.50; P = 0.083) G:F than pigs on the control (T1) and T2 diets, respectively. Relative to pigs on the T1 diet, ADG (0.796 vs 0.799 kg) and G:F (0.47 vs 0.48) of pigs fed the T2 diet were similar (P ˃0.10). Furthermore, pigs fed T4 and T3 diets did not differ in terms of ADFI (2.15 vs 2.14 kg; P = 0.994), ADG (0.804 vs 0.826 kg; P = 0.235), and G:F (0.48 vs 0.50; P = 0.260). Dietary treatments did not affect final BW, hot carcass weight, carcass yield, BF thickness, rib eye area, and percent lean (P ˃0.10). Based on performance criteria, these findings suggest OFS seaweed blend can replace either antibiotic growth promotors or pharmacological levels of zinc oxide in swine feeds.